Power etiquette : what you don't know can kill your career - Casperson, Dana May (AMACOM/ American Management Association International, 1999)
No-nonsense guidance to a crucial set of personal career skills. Can table manners make or break a megamerger? Can a faxing faux-pas derail a promising business relationship? Can an improper introduction cost you a client? Can manners (or lack of them) really kill a career? Absolutely. In an era when companies are competing on the basis of service, manners are much more than a social nicety - they're a crucial business skill. In fact, good manners are good business. This no-nonsense "manners reference" refreshes readers on everyday etiquette and makes sure they're on their best behavior. It provides quick guidance on such pertinent and timely topics as: * telephone and e-mail etiquette * table manners *grooming and business dress * written communications * gift giving * resumes and interviews * making introductions * public speaking * networking, and more.